MAKNA BAAYUN MAULUD PADA MASYARAKAT BANUA HALAT KABUPATEN TAPIN - ., Sarwani (Alhadharah: Jurnal Ilmu Dakwah, 2017)
Baayun Maulud is a traditional form of communication in society Banua Halat Tapin district. Formerly from the culture of religious people Keharingan is called the Baayun Children. Then, through a process of Islamization by religious leaders, Now Baayun Children called Baayun Maulud. The purpose of this research was determine and describe the meaning which is contained of Baayun Maulud society Banua Halat Tapin district. The research approach used in this study was qualitative approach, with etnography of communication as the method and descriptive as the type. The data were obtained from observation, interview and documentation. The result of this study showed that Baayun Maulud in Banua Halat society implies the goodness in living a wide variety of life. Baayun Maulud also interpreted as a form of gratitude to the God, nowaday Baayun Maulud not only for childrens but various circle, expecially parents who have nazar. Aside from being nazar Baayun Maulud in Banua Halat society also used as a medium to tighten silaturrahmi.